Binder‐free carbon‐coated nanocotton transition metal oxides integrated anodes by laser surface ablation for lithium‐ion batteries. (18th June 2019) - Liang, Peng; Zhang, Hongjun; Pan, Boyu; Su, Yibo; Wang, Chang‐An; Zhong, Minlin
Abstract : In this paper, an efficient laser surface ablation strategy for producing binder‐free carbon‐coated nanocotton CoO‐Co integrated anode is reported. The fabrication process introduces in‐situ growing nanocotton‐like CoO on the surface of Co foil via ablating with a nanosecond laser. After that, coated with dopamine as carbon source, the CoO‐Co composite foil is heated in Argon atmosphere to form a CoO@C‐Co foil as an anode of LIB. The laser surface ablation exhibits high fabrication speed ( 10 minutes) and significantly reduces the processing time. The obtained binder‐free CoO@C‐Co integrated anode shows a unique cotton‐like villous structure with large specific surface area and an active material/current collector integrated architecture, which provides a stabilized rapid electronic conduction path. When tested as an anode for LIBs, the CoO@C‐Co integrated anode possesses superior performance: First discharge capacity of 1301.5 mAh g −1 is achieved at a current density of 0.1 A g −1 . Also at a high current density of 1.5 A g −1, the second discharge capacity of 791.7 mAh g −1 is achieved. After 800 cycles, reversible capacities of 799.8 mAh g −1 can still be achieved with an average coulombic efficiency of nearly 100%. In addition, this strategy is suitable for the production of other carbon coated transition metal oxides integrated anodes, such as NiO@C‐Ni, Fe2 O3 /Fe3 O4 @C‐Fe, and CuO/Cu2 O@C‐Cu integrated anodes.